Co‐La‐Based Hole‐Transporting Layers for Binary Organic Solar Cells with 18.82 % Efficiency. (16th December 2022) - Zhang, Guangcong; Chen, Qiaomei; Zhang, Zhou; Fang, Jie; Zhao, Chaowei; Wei, Yen; Li, Weiwei
Abstract: Poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is a widely used hole transporting layer (HTL) in organic solar cells (OSCs), but its acidity severely reduces the stability of devices. Until now, very few HTLs were developed to replace PEDOT:PSS toward stable and high‐performance OSCs. Herein, a new cobalt‐lanthanum (Co‐La) inorganic system was reported as HTL to show a high conversion efficiency (PCE) of 18.82 %, which is among the top PCEs in binary OSCs. Since electron‐rich outer shell of La atom can interact with Co atom to form charge transfer complex, the work function and conductivity of the Co‐La system could be simultaneously enhanced compared to Co or La‐based HTLs. This Co‐La system could also be applied into other OSCs to show high performance. All these results demonstrate that binary Co‐La systems as HTL can efficiently tackle the issue in hole transporting and show powerful application in OSCs to replace PEDOT:PSS. Abstract : Low‐temperature solution‐processed Co‐La‐based hole transporting layers were developed for organic solar cells with high power conversion efficiency (18.82 %), superior reproductivity and long‐term stability.